Chapter Translating Heritage Tourism in Italy. Churches and Palaces of the Ducato Estense - Aragrande, Gaia (Lessico multilingue dei Beni Culturali, 2023)
This work reports on an ongoing Italian-English translation project that began in 2018. This project aims at compiling a learner corpus and involves a Government Department as client and a selected group of MA students as translators. Texts to be translated focus on cultural heritage and are targeted to the international tourism market. This chapter centers on a sub-corpus that focuses on churches and palaces of the House of the Estense. This chapter draws attention to the target texts of our corpus. Starting from the extraction of specific terms in the source texts, target texts are analysed quantitatively and qualitatively in order to identify translation strategies and frequent mistakes with the aim of contributing to the translation of art and architecture for heritage tourism.